Strategi Peningkatan Nilai Maturitas Sistem Pengendalian Intern Pemerintah Pada Kementerian Pertanian - Andreanthony, Yosua Meditia; Silitonga, Niko (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2024)
This research was conducted to find out and analyze in developing a strategy to increase the maturity of SPIP within the Government by using sub-elements of SPIP itself, namely Leadership Commitment, Policies and Regulations, Human Resources, Innovation Development and Rewards and Punishment. The research uses a quantitative research methodology with descriptive analysis. The sampling technique uses purposive sampling. A sample of 120 people was obtained. The analysis technique used regression by testing using SPSS software, hypothesis testing using the T test and F test showed that (1) Leadership's commitment did not have a significant effect on the maturity value of SPIP (2) Human Policy and Regulation had a significant effect on the maturity value of SPIP (3) Human Resources had a significant effect on the maturity value of SPIP (4) Innovation had a significant effect on the maturity value of SPIP (5) Provision of Reward and Punishment did not have a significant effect on the maturity value of SPIP